Characterization of Orange Peel Extract and Its Potential Protective Effect against Aluminum Chloride-Induced Alzheimer's Disease - Nourhan Mohammad Abd El-Aziz; Mohamed Gamal Shehata; Tawfiq Alsulami; Ahmed Noah Badr; Marwa Ramadan Elbakatoshy; Hatem Salama Ali; Sobhy Ahmed El-Sohaimy (MDPI AG, 2022)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder without a cure. Hence, developing an effective treatment or protective agent is crucial for public health. The present study aims to characterize orange peel extract (OPE) through in vitro and in silico studies. Furthermore, it examines the protective effect of OPE against experimentally-induced Alzheimer's disease in rats. The total phenolic and flavonoid content of OPE was 255.86 ± 1.77 and 52.06 ± 1.74 (mg/100 g), respectively. Gallic acid, the common polyphenol in OPE detected by HPLC was 3388.60 μg/100 g. OPE antioxidant IC50 was 67.90 ± 1.05, 60.48 ± 0.91, and 63.70 ± 0.30 by DPPH, ABTS and Hydroxyl radical scavenging activity methods, respectively. In vitro anti-acetylcholinesterase (AChE) IC50 was 0.87 ± 0.025 mg/mL for OPE and 2.45 ± 0.001 mg/mL for gallic acid. Molecular docking analysis for human AChE (4EY7) with donepezil, gallic acid, and acetylcholine showed binding energy ΔG values of −9.47, −3.72, and −5.69 Kcal/mol, respectively. Aluminum chloride injection (70 mg/Kg/day for 6 weeks) induced Alzheimer's-like disease in male rats. OPE (100 and 200 mg/kg/d) and gallic acid (50 mg/kg/d) were administered orally to experimental animals for 6 weeks in addition to aluminum chloride injection (as protective). OPE was found to protect against aluminum chloride-induced neuronal damage by decreasing both gene expression and activity of acetylcholinesterase (AChE) and a decrease in amyloid beta (Aβ42) protein level, thiobarbituric acid-reactive substances (TBARS), and nitric oxide (NO), and increased reduced glutathione (GSH) level and activity of the antioxidant enzymes in the brain tissues. Additionally, gene expressions for amyloid precursor protein (APP) and beta secretase enzyme (BACE1) were downregulated, whereas those for presinilin-2 (PSEN2) and beta cell lymphoma-2 (BCL2) were upregulated. Furthermore, the reverse of mitochondrial alternation and restored brain ultrastructure might underlie neuronal dysfunction in AD. In conclusion, our exploration of the neuroprotective effect of OPE in vivo reveals that OPE may be helpful in ameliorating brain oxidative stress, hence protecting from Alzheimer's disease progression.